2021
DOI: 10.3390/foods10061436
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effectiveness of Disinfectants Used in Meat-Processing Facilities to Control Clostridium sporogenes and Clostridioides difficile Spores

Abstract: Spore-forming bacteria are a major concern for the food industry as they cause both spoilage and food safety issues. Moreover, as they are more resistant than vegetative cells, their removal from the food processing environment may be difficult to achieve. This study investigated the efficacy of the ten most commonly used disinfectant agents (assigned 1–10), used at the recommended concentrations in the meat industry, for their ability to eliminate Clostridium sporogenes and Clostridioides difficile spores. Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Treatment 3 (peroxymonosulphate, sulphamic acid and troclosene sodium) was not as effective as treatments 1 and 2. This was unexpected as previous studies have suggested that peroxymonosulphate, an oxidizing agent, has sporicidal activity [17,41] even in the presence of moderate organic debris [50].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Treatment 3 (peroxymonosulphate, sulphamic acid and troclosene sodium) was not as effective as treatments 1 and 2. This was unexpected as previous studies have suggested that peroxymonosulphate, an oxidizing agent, has sporicidal activity [17,41] even in the presence of moderate organic debris [50].…”
Section: Discussionmentioning
confidence: 80%
“…Peracetic acid decomposes to hydrogen peroxide and acetic acid and is more potent than hydrogen peroxide alone in the presence of organic matter [14]. A recent study has demonstrated sporicidal formulations containing hydrogen peroxide, peracetic acid and acetic acid are effective against C. sporogenes and C. difficile spores with D values as low as 2.1 and 5.3 min, respectively [41]. This formulation has strong antimicrobial activity [17,21,42], including against Clostridial spores [42][43][44][45] and has been recommended for the control of BPS Clostridium spores [10,13].…”
Section: Discussionmentioning
confidence: 99%
“…This result was also seen in B. subtilis where 0.3% peracetic acid at 70°C for 5 and 10 min was not able to attain >5 log CFU/ml. This could possibly be due to the attributes of Gram‐positive having a thick peptidoglycan for the vegetative cells and protective mechanism of spore coats for the endospore that could resist the action of low concentration of peracetic acid (Eissa et al., 2014; McSharry et al., 2021). This also shows that the action of peracetic acid mostly relies on its optimal concentration to exhibit its effectiveness (Eissa et al., 2014; Katara et al., 2016; Korukluoglu et al., 2006; Sandle et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Such foodstuffs make public health concerns, especially for children, vulnerable elderly, immunocompromised individuals, and pregnant women. Additionally, the higher resistance of spores than vegetative forms of C. difficile makes it difficult to destroy the bacterium ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…About 60% of animal-related diseases in humans and approximately 75% of new human infections are transmitted to humans through vertebrates ( 17 ). Although no reports have confirmed that C. difficile is food-borne or zoonotic, it is necessary to observe food health and safety protocols and establish food safety management systems such as Good Manufacturing Principles (GMP), Good Hygiene Principles (GHP) and Hazard Analysis and Critical Control Point (HACCP) system ( 4 , 16 ).…”
Section: Discussionmentioning
confidence: 99%